An investigation into the role of clinical education in preparing undergraduate physiotherapy students for professional practice in the Emirate of Abu Dhabi - Ramakrishnan, Senthilnathan (2022)
Background: Clinical education is an integral part of physiotherapy education. In clinical placements students encounter complex cases and challenging circumstances and learn to withstand and overcome these situations. These experiences are vital for graduates’ readiness for professional practice. Purpose: The aim of this research was to understand the contribution of clinical education in preparing undergraduate physiotherapy students for professional practice. Methods: This study took a qualitative methods approach and interviews were used to collect data from physiotherapy students and clinical educators. Participant responses were audio recorded and verbatim transcribed for analysis. NVivo12 was used for analysis of data. Results: Thematic analysis of participants’ interviews confirmed that the real-world experience was useful in developing reflective practice, exposure to evidence-based practice and autonomous practice, opportunity to develop interpersonal skills and develop open-mindedness for feedback which are all vital for professional practice. Conclusion: It was evident from the findings that clinical education played a crucial role in preparing the physiotherapy students for entry-level physiotherapist roles.